2015
DOI: 10.1177/1463499615605221
|View full text |Cite
|
Sign up to set email alerts
|

‘Because life it selfe is but motion’: Toward an anthropology of mobility

Abstract: Over the last two decades, mobility has gained new prominence within anthropology, particularly in theories of globalization, immigration, and subjectivity. At stake in all of the recent ethnographic and archaeological work on mobility is not just how anthropologists conceptualize mobility, but also how we conceptualize the political. Many discussions of mobile subjects have seemed to challenge traditional understandings of the political that are synonymous with a monolithic state and a stable, sedentary subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 99 publications
0
9
0
1
Order By: Relevance
“…Mobility is more than just physical movement (Salazar 2017, 5). Lelièvre and Marshall (2015) differentiate between the two by deeming movement to be an object of observation while mobility is an object of study. According to Lelièvre and Marshall, the former is therefore abstract and devoid of meaning, whereas the latter is socially constructed.…”
Section: Mobility: Physical and Social Movementsmentioning
confidence: 99%
“…Mobility is more than just physical movement (Salazar 2017, 5). Lelièvre and Marshall (2015) differentiate between the two by deeming movement to be an object of observation while mobility is an object of study. According to Lelièvre and Marshall, the former is therefore abstract and devoid of meaning, whereas the latter is socially constructed.…”
Section: Mobility: Physical and Social Movementsmentioning
confidence: 99%
“…From mission “fortresses” described by borderland historian Herbert Bolton (1917:51) to the prison-missions narrated in the present (Madley 2019), popularized scholarly accounts of colonialism falsely depicted the immobility of Indigenous peoples even when living Indigenous peoples—and mounting archaeological evidence—suggest otherwise. Crossing ancestral lands and waters, Michelle Lelièvre and Maureen Marshall (2015) note, the mobility of Mi'kmaq people represented important political acts of sovereignty and emplacement that distressed Catholic missionaries operating in Nova Scotia. Mobilization to mesa-top refuges ensured access to spaces of protection and spiritual strength for Indigenous peoples throughout the Southwest following the 1680 Pueblo Revolt (e.g., Aguilar and Preucel 2019).…”
Section: Epidemic Disease Among Indigenous Peoples Black Communitiesmentioning
confidence: 99%
“…For example, Williams’ research in Thanet, south east England, showed that “help-seeking behaviour and life strategies were significantly influenced by the social networks of individuals, even when those networks were transnational and when individuals had little or no apparent local support” (2006, p. 866; Varvantakis et al , 2019). As Lelièvre and Marshall (2015, p. 435) argue “ethnographers of transnational migration have demonstrated that even the most disenfranchised subjects creatively network, wire money, and otherwise create ‘spaces of connectivity’”. In a similar vein, Papadopoulos and Tsianos (2014, p. 190) describe the undulating relationships and practices of social support of migration as a “mobile commons”.…”
Section: Everyday Life and Mental Health Social Supportmentioning
confidence: 99%